Climate and topographic drivers of species and functional diversity in subtropical shrublands of Guangdong, China - Xuan Luo; Mengmeng Yang; Muhammad Sadiq Khan; Wanxuan Huang; Shizhong Liu; Feiyong Liao; Yuelin Li (Ecological Indicators)
Subtropical shrubland ecosystems in southern China are increasingly threatened by degradation under global climate change. However, the mechanisms by which environmental gradients shape species and functional diversity remain poorly understood. In this study, we examined spatial patterns of biodiversity across 15 shrubland communities in Guangdong Province using taxonomic and functional diversity indices, regression analysis, Pearson correlation, Redundancy analysis (RDA), and MaxEnt modeling. We found that species and functional diversity declined significantly along the longitudinal gradient, while species diversity increased and functional diversity decreased with increasing latitude. Precipitation during the wettest month explained 55.2 % of the variation in species diversity (p < 0.05). For functional diversity, precipitation during the driest month and the minimum temperature of the coldest month accounted for 55.2 % and 10.2 % of the variance, respectively (p < 0.05). Soil nutrients and topographic variables also contributed to spatial heterogeneity in diversity patterns. MaxEnt models predicted species distributions with high accuracy (mean AUC > 0.96). These findings highlight the dominant roles of climatic and edaphic factors in structuring shrubland biodiversity, providing a robust foundation for conservation planning and sustainable ecosystem management in subtropical regions.